Emergence, prevalence, and evolution of H5N8 avian influenza viruses in central China, 2020. Issue 1 (31st December 2022) - Li, Xiang; Lv, Xinru; Li, Yi; Xie, Linhong; Peng, Peng; An, Qing; Fu, Tian; Qin, Siyuan; Cui, Yuan; Zhang, Chengbo; Qin, Rongxiu; Qu, Fengyi; et al.
ABSTRACT: Highly pathogenic influenza A(H5N8) viruses have caused several worldwide outbreaks in birds and are able cross the species barrier to infect humans, posing a substantial threat to public health. After the first detection of H5N8 viruses in deceased swans in Inner Mongolia, we performed early warning and active monitoring along swan migration routes in central China. We isolated and sequenced 42 avian influenza viruses, including 40 H5N8 viruses, 1 H5N2 virus, and 1 H9N2 virus, in central China. Our H5N8 viruses isolated in swan stopover sites and wintering grounds showed high nucleotide homologies in the whole genome, revealing a common evolutionary source. Phylogenetic analysis revealed that the H5 viruses of clade 2.3.4.4b prevalent in 2020 have further diverged into two sub-clades: b1 and b2. The phylogeographic analysis also showed that the viruses of sub-clade b2 most likely originated from poultry in Russia. Notably, whooper swans were found to be responsible for the introduction of sub-clade b2 viruses in central China; whooper and tundra swans play a role in viral spread in the Yellow River Basin and the Yangtze River Basin, respectively. Our findings highlight swans as an indicator species for transborder spreading and monitoring of the H5N8 virus.